Self-regulated learning in mathematics online learning environment: a systematic review - Letchumanan, Malathi; Husain, Sharifah Kartini Said; Ayub, Ahmad Fauzi Mohd (Grand Canyon University, 2024)
Learning mathematics in an online learning environment has unique challenges. Success in an online mathematics learning environment depends on a student’s self-regulating ability. This systematic review provides the scholarly community with a synthesis of current self-regulated learning (SRL) strategies of students in the mathematics online learning environment. We looked at research from 2014 to 2022 regarding the approaches, purposes, outcomes, and limitations of these studies. Our findings indicate that most of the studies focused on the effect of SRL on student achievement. The results reveal that 88.2% of the studies used a quantitative approach and 41.1% employed high-school students as study samples. In addition, most of the studies used questionnaires to collect data and indicated that their limitation was the narrow study context. We encourage learning institutions to integrate SRL strategies in mathematics online learning environments to improve the quality of education.